RADT-22. CONCURRENT TTFIELDS (200 KHZ) WITH CHEMORADIATION FOR PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA MAY INCREASE THE RATE OF PSEUDOPROGRESSION: ANALYSIS OF A PILOT CLINICAL TRIAL. (12th November 2021) - Niazi, Muneeb; Taylor, James; Miller, Ryan; Ali, Ayesha S; Bar-Ad, Voichita; Martinez, Nina, L; Glass, Jon; Alnahhas, Iyad; Andrews, David; Judy, Kevin; Evans, James; Farrell, Christopher; et al.
Abstract: OBJECTIVE: The standard of care for the adjuvant treatment of glioblastoma is concurrent chemoradiation, maintenance temozolomide, and Tumor Treating Fields (TTFields). TTFields may reversibly impact the blood-brain barrier, most significantly at 100 kHz. We hypothesized that this may increase the rate of pseudoprogression (PsP) in patients who receive concurrent chemoradiation with TTFields (200 kHz). METHODS: This is a single arm pilot study (clinicaltrials.gov Identifier: NCT03477110). Patients with newly diagnosed glioblastoma, age ≥ 18 years, and KPS ≥ 60 were eligible. They received concurrent temozolomide (75 mg/m 2 ), scalp-sparing radiation (60 Gy in 30 fractions), and TTFields (200 kHz). Radiation was delivered through the TTFields arrays. PsP was defined as radiographic progression of enhancing lesions without clinical decline that improved or remained stable upon subsequent imaging. The rate of PsP was determined by an evaluation of the 2 nd MRI at our multidisciplinary tumor board after the completion of trimodality treatment. These findings were confirmed with official radiology reports. RESULTS: 30 patients were enrolled. Of these, 29 had imaging available for evaluation. Male-to-female ratio was 20:10. Median follow-up was 11.6 months (1.6-22.4 months), median age was 58 years (19-77 years), and median KPS was 90 (70-100). 20 (66.7%) patients had unmethylated and 10 (33.3%) had methylated MGMT promotor. Median time from surgery to initiation of radiation was 34 days (26-49 days). Median time from completion of trimodality treatment to 2 nd follow-up MRI was 90 days (29-109 days). 15/29 (51.7%) patients had PsP. Patients with methylated and unmethylated MGMT promotor had 50.0% (5/10) and 52.6% (10/19) rates of progression respectively. CONCLUSIONS: 51.7% of the patients who received concurrent chemoradiation with TTFields demonstrated PsP. The incidence is greater than historical reports. However, these findings should be explored in larger cohorts as this study was limited by a small sample size.